Relación entre el voluntariado ambiental y el bienestar subjetivo: un análisis del caso ecuatoriano durante el periodo 2022 - Guevara Segura, Anais Betty (2024)
According to the Organization for Economic Cooperation and Development (OECD), in Ecuador, subjective well-being has decreased from 0,5 to 0,8 points (OECD, 2020). However, CO2 emissions per capita in Ecuador have reached a level of 2,59 tons per inhabitant, reflecting an increase in environmental pollution (Datosmacro, 2024). This situation is further exacerbated by the fact that the Instituto Nacional de Estadísticas y Censos (INEC) highlights that environmental volunteering accounted for only 8,43% of environmental activities in Ecuador (INEC, 2019). Therefore, the general objective of this study is to examine the relationship between participation in environmental volunteering and individual subjective well-being in Ecuador during the year 2022, using statistical and econometric techniques, in order to give policies to improve individual and subjective well-being through participation in environmental volunteering. In this context, data corresponding in October 2022 were used, collected from the National Survey of Employment, Unemployment, and Underemployment (ENEMDU) of Ecuador. Econometric models such as “Ordered Probit” and random parameters were employed. The main results show that Ecuadorian household leaders who participate in these activities gain experience greater personal satisfaction; likewise, using random parameters, it was identified that 95% of individuals who engage in environmental volunteering show a positive correlation with their level of subjective well-being, while factors such as being male, identifying as mestizo, cohabitation, and living in urban areas influenced by subjective well-being. Finally, comprehensive strategies are proposed in order to develop specific educational campaigns addressing the cost-benefit perceptions that affect low participation in environmental volunteering, considering the socioeconomic and demographic dimensions of household leaders in Ecuador.